Polyarteritis nodosa in north India: clinical manifestations and outcomes. (19th December 2016) - Sharma, Aman; Pinto, Benzeeta; Dhooria, Aadhaar; Rathi, Manish; Singhal, Manphool; Dhir, Varun; Sharma, Kusum; Parkash, Mahesh; Modi, Manish; Vijayvergiya, Rajesh; Sinha, Saroj K.; Nada, Ritambhra; et al.
Abstract: Objective: There has been a significant decrease in the number of published reports of classical polyarteritis nodosa (PAN) in the post‐Chapel Hill consensus conference (CHCC) nomenclature era with only two series published from Asia. We report a case series of PAN from north India. Patients and Methods: A retrospective study of all patients diagnosed to have PAN according to American College of Rheumatology criteria/CHCC nomenclature. The details of clinical presentation, investigation findings, treatment details and outcomes were noted from the records. These findings between the hepatitis B positive and negative groups were compared. Results: Twenty‐seven patients (20 male, seven female) were diagnosed as having PAN, out of which seven (25.9%) were hepatitis B surface antigen positive. Nervous system involvement was most common with 24 patients (88.9%) having mononeuritis multiplex. Weight loss was present in 20 (74%), fever in 14 (51.9%), renal involvement in 16 (59.3%), cutaneous in nine (33.3%), peripheral gangrene in eight (29.6%), gastrointestinal (GI) involvement in eight (29.6%), testicular pain in 6/20 (30%) and cardiac involvement in four (14.8%). Twenty‐three (85.2%) patients recovered, three died (11.1%) and one was lost to follow‐up. Median follow‐up duration was 37 (interquartile range 22.00–69.75) months. The cumulative survival was 114.16 months (95% CI: 98.27–129.95). There was no significant difference in five factor score (FFS) or revised FFS between those patients who died and those who survived ( P = 0.248, 0.894, respectively). Hepatitis B‐related PAN had a lower FFS compared to non‐hepatitis B‐related PAN ( P = 0.039). No other significant differences were noted between the two groups. Conclusion: In comparison to classic PAN in other populations, classic PAN in north India is associated with higher neurological involvement and lower GI involvement.